El hombre que ríe Based on a Novel by Victor Hugo - Hugo, Victor
Movie villains smile so compulsively because it creates a creepy disconnect between their mouth and their eyes. Imagine, however, a good man, condemned to smile widely for an entire lifetime. Such a creature would be bullied as a child and shunned as an adult. "The Man Who Laughs" (1928), one of the final treasures of German silent Expressionism, is about such a man. His name is Gwynplaine. His father was a nobleman. Orphaned as a child, he is captured by outlaws who use a knife to carve his face into a hideous grin. Disfigured, alone, he rescues a baby girl, and together they are raised by a fatherly vaudeville producer. As adults, they star in the producer's sideshow and fall in love. Because she is blind, she does not know about his grin. This story, set in 17th century England, was written by Victor Hugo, and made into one of the last (almost) silent films by Paul Leni, the director of "Waxworks" (1927) and "The Cat and the Canary" (1929). He was an art director who grew up in Germany during the era of Expressionism - of films dominated by twisted sets and characters, harsh angles, deep shadows, careening staircases. He and his star, the great Conrad Veidt, two Jewish refugees, made the film for Universal in Hollywood. [www.rogerebert.com]